Comparison of Cefotaxime with Ofloxacin in Treatment of Spontaneous Bacterial Peritonitis in Liver Cirrhosis Patients - Laiq Said Bacha, Tarique Ali, Fazli Rabbi, Saadia Zainab, Muhammad Salman Tahir, Omar Ahsan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Ofloxacin (Quinolone) is effective antibiotic against Gram-negative bacteria and has high bioavailability with minimum duration of therapy. Objective: The study aimed to compare the ofloxacin and cefotaxime efficacy in treatment of spontaneous bacterial peritonitis in Liver cirrhosis subjects. Study design: It is a randomized controlled trail study conducted at Department of Medicine, Federal Govt Polyclinic Hospital Islamabad, from August 2021 January 2022. Material and Methods: A total of one hundred and seventy six (n=176) adult subjects of both gender between age 18-65 years presented with ascitic fluid infection with PMN counts ≥ 250 cells/mm3 were enrolled in the study. The 88 subjects were randomly assigned by lottery method into Group I (Ofloxacin) and group II (Cefotaxime). Outcome of interventions was assessed clinically and through lab investigations (PMN counts) at day 3 and day 5. Culture reports were available at 5th day. The collected data was analyzed statistically by the SPSS software. Results: Mean age was 53.1 years ± 8.1 SD in group I while it was 53.2 years ± 8.4 SD in group II. Abdominal pain was the most frequent complaint (70.5% in group I and 67% in group II) followed by nausea and fever. On day 3, efficacy was 44.3% in group I and 39.8% in group II. On day 5, efficacy was observed to be 90.9% in group I and 80.7% in group II. All the subjects were sensitive to the antibiotics they were receiving. Therapy was not proved to be efficacious in 25 subjects in group I and 17 in group II. Resistant Escherichia coli was the most frequent organism in these cases. Therapy was modified as per sensitivity reports. No mortality was observed in both groups during hospital stay. Both the therapies were well tolerated and no significant side effects were observed in both groups. Conclusions: The efficacy of Ofloxacin was significantly better on day 5 compared to Cefotaxime in subjects. Ofloxacin is a better option than Cefotaxime in treating spontaneous bacterial peritonitis. However, further studies with larger sample size required. Keywords: Ofloxacin, Cefotaxime, bacterial peritonitis, antibiotics.